Caracterização petrográfica e tecnológica de granitos ornamentais do stock granítico Serra do Barriga, Sobral/CE - Mattos, Irani Clezar; Artur, Antonio Carlos [UNESP]; Nogueira Neto, José De Araújo (My University, 2013)
Petrographic analysis and technological behaviour of four varieties of granitic dimension stones from Serra da Barriga stock, in NNW Ceará State, Brazil, are presented in this work. The investigated rock types are commercially known as Rosa Iracema, Rosa Olinda, Branco Savana and Branco Cristal Quartzo and are classified as isotropic, inequigranular syenogranites and monzogranites, medium to coarse grained, with colours ranging between pink and white. The technological tests results, of physical and mechanical parameters were very similar between the four rock samples and put the analysed granites as having good technological properties, suitable for coatings for both indoors and outdoors environments. The correlations between rock physical and mechanical characteristics results, show the importance of mineralogical, textural and structural aspects of some dimension stone granites technological properties. Among the verified most influence petrographic parameters, stand out the rocks coarse grains, quartz content, microcracking level, mineral weathering, which control, higher or lower level, apparent porosity, water absorption, mechanical resistance (uniaxial and flexural strength), impact, Amsler abrasion, thermal expansion and ultrasonic waves propagation, of that granites.
Petrographical and technological characterization of granites from Serra do Barriga stock, Sobral/CE
Keywords: Dimension stones; Petrography; Serra do Barriga stock; Technological characterization